Using Co-segregation and Loss of Heterozygosity Analysis to Define the Pathogenicity of Unclassified Variants in Hereditary Breast Cancer Patients - Grasel, Rebeca Silveira; Felicio, Paula Silva; de Paula, André Escremim; Campacci, Natalia; Garcia, Felipe Antônio de Oliveira; de Andrade, Edilene Santos; Evangelista, Adriane Feijó; Fernandes, Gabriela Carvalho; Sabato, Cristina da Silva; De Marchi, Pedro; Souza, Cristiano de Pádua; de Paula, Cláudia Alessandra Andrade; et al. (Frontiers in Oncology, 2020)
The use of gene panels introduces a new dilemma in the genetics field due to the high frequency of variants of uncertain significance (VUS). The objective of this study was to provide evidence that may help in the classification of these germline variants in terms of their clinical impact and association with the disease in question. A total of 52 unrelated women at-risk for HBOC and negative for BRCA1/BRCA2 pathogenic variants were evaluated through a gene panel comprising 14 breast/ovarian cancer susceptibility genes. Of the 453 germline variants identified, 15 variants (classes 3, 4 and 5) in the ATM, BRIP1, CHEK2, MRE11A, MUTHY, PALB2, RAD50 and RAD51C genes were evaluated via databases, co-segregation studies and loss of heterozygosity in the tumor. The co-segregation analysis allowed the establishment of an association with the presence of variants and the risk of cancer for variant c.316C>T in the BRIP1 gene. Four variants of uncertain significance showed loss of heterozygosity in the tumor (ATM c.4709T>C; CHEK2 c.1036C>T; PALB2 c.1001A>G and RAD50 c.281T>C), which is an indication of pathogenicity. Thus, the present study provides novel evidence that favors the association of variants in moderate-risk genes with the development of hereditary breast cancer.